Contribution of Woman Ulama in The Digital Era - Badrah Uyuni; Khairan Muhammad Arief; Mohammad Adnan (Research Synergy Foundation, 2023)
Education is essential, especially in an era of disruption and moral deterioration. Consequently, there is a need for multiple forms of religious teaching, particularly in the digital sphere. Women must also be able to access the digital domain, as they constitute most of the religious population. Only women have a greater understanding of women's issues. Hence, the empowerment of Muslim women requires the assistance of female digital experts. The study tried to show that many women also educate and spread Islamic teaching in the digital sector. Even though there is a concept of women in public spaces as aurat, women still show their existence and can keep up with the times. This research was conducted by a case study using a descriptive analysis method through a qualitative approach. The primary data sources are observation, interviews, and documentation with research samples of 10 viral female clerics on social media. It shows that the concept of women appearing in public spaces does not prevent da'wah and social roles, as the existence of women is closely related to their actions for society. Furthermore, preachers in the current era need digital, technological, and human literacy to survive. Nevertheless, they must imitate the previous female ulama and posit them as ideal role models: acting as muharrik (activator), murabbi and mu'allim (educator), munadzzim (organiser/leader), mura'i (guardian), and munasik (controller) for the ummah at the same time. In research on women, gender theory is often used as the basis for analysis; nonetheless, this study primarily concentrates on the theoretical aspects of the female ulama's contribution in the digital era, seeking to comprehend how they adeptly acquire digital literacy to convert religious values into digital formats.